Faktor Berkaitan dengan Stunting dan Wasting pada Pasien Onkologi Anak: Faktor Berkaitan dengan Stunting dan Wasting pada Pasien Onkologi Anak - Maya Utami Widhianti; Listiyani Eka Tyastuti; Meika Rahmawati Arifah; Karima Rizqi Alviani; Hagnyonowati (Amerta Nutrition, 2022)
Background: Stunting and wasting occurring together in the pediatric oncology population are common and have an adverse effect on them. However, there is limited study regarding stunting and wasting of oncology pediatric in Indonesia. Objectives: This study aims to determine associated factors of stunting and wasting in pediatric oncology population. Methods: A retrospective cross-sectional study was conducted at Kariadi General Hospital. Subjects were pediatric oncology inpatients during 2020-2022 aged 1-5 years. Stunting and wasting were defined as height for age < -2 SD and weight for height < -2 SD. The category of age, gender, parents’ employment status, parents’ age, residential area, payment arrangement, energy intake, and cancer type were analyzed for the relationship by chi-square and regression logistic. Results: Out of 194 patients, 52.1 % was male, 78.4% was aged 2 to 5 years. The prevalence of stunting, wasting, and stunting and wasting occurring together in this population was 31.4 %, 39.2 % dan 13.4 %, respectively. In multivariate analysis, energy intake less than 75 % was associated with stunting and wasting (OR = 2.75, 95 % CI = 1.14-6.58, p = 0.023). Conclusions: The factor associated with stunting and wasting occurring together in pediatric patients with cancer is energy intake of less than 75 %.